The role of hypercoagulability in the development of osteonecrosis of the femoral head - Lykissas, Marios G. (PAGEPress Publications, 2012)
Despite the large number of the outstanding researches, pathogenesis of osteonecrosis remains unknown. During the last decades the hypothesis that increased intravascular coagulation may be the pathogenetic mechanism which leads to osteonecrosis is gaining constantly support. Both primary factors of hyper-coagulability, such as resistance to activated protein C, protein C and protein S deficiency, low levels of tissue plasminogen activator, high levels of plasminogen activator inhibitor, von Willebrand factor, lipoprotein (a), and secondary factors of hypercoagulability with factors potentially activating intravascular coagulation, such as pregnancy, antiphospholipid antibodies, systemic lupus erythematosus, hemoglobinopathies and sickle cell disease, and hemato-oncologic diseases are discussed in this article. Although coagulation abnormalities in patients with hip osteonecrosis might represent increased risk factors for the development of bone necrosis by predisposing the patient to thromboembolic phenomena, further investigation is needed to indicate the definite correlation between factors leading to increased intravascular coagulation and pathogenesis of osteonecrosis.